Critical relationship between biodiesel fuel properties and degradation of fuel delivery materials of a diesel engine - Davannendran, Chandran *; Gan, Suyin; Lau, Harrison Lik Nang; Revathi, Raviadaran; Salim, Mohammed; Khalid, Mohammad * (Elsevier, 2018)
This work aims to disseminate the critical relationship present between biodiesel fuel properties and the degradation of commonly present fuel delivery materials (FDM) of a diesel engine. This was achieved by quantifying the adverse eﬀects of palm biodiesel fuel exposure towards aluminium, galvanized steel, stainless steel, ﬂuoroelastomer, silicone rubber and nylon under novel immersion method. Under the novel immersion method which was designed to resemble the biodiesel fuel deterioration under diesel engine operation, fuel renewal was incorporatedinthetypicalstandardmethods.Theutilizedfuelrenewaldurationswere108hand192hformetal and elastomers, respectively. Through this, the resulting biodiesel fuel properties under diesel engine operation were primarily simulated under the immersion methods. The experimentations were carried out for 540h and 960h for metals and elastomers, respectively, at 100°C. Based on the obtained results, as well as the comparisons madetoanexistingstudy, galvanizedsteel,aluminium andstainlesssteel hadlowercorrosionrateby33%, 74% and 80%, respectively, as compared to copper. On the other hand, 26%, 78% and 106% lower volume changes were determined for silicone rubber, ﬂuoroelastomer and nylon, respectively, as compared to nitrile rubber. Signiﬁcantly lower degradation rate of up to 20 times for metals and 5 times for elastomers were critically obtained under novel immersion method as compared to under typical immersion methods from existing studies. This demonstrates that through the employment of novel immersion method which simulates biodiesel fuel properties as per under diesel engine operation, much better compatibility is deemed present between biodiesel fuel and FDM contrasting to the existing studies.